Autonomic receptors and nitric‑oxide involvements in mediating vasorelaxation effect induced by syzygium polyanthum leaves extract - Ismail, Azlini; Wan Ahmad, Wan Amir Nizam (Wolters Kluwer - Medknow Publications, 2017)
Context: Syzygium polyanthum (Wight) Walp leaves are traditionally used by Malays for treating hypertension. Our previous study showed that aqueous extract of S. polyanthum (AESP) and methanolic extract of S. polyanthum (MESP) leaves significantly reduced blood pressure of normotensive Wistar‑Kyoto (WKY) and spontaneously hypertensive rats (SHR). Aims: This study aimed to investigate their vasorelaxation potential and the possible involvement of autonomic receptors and nitric oxide in mediating their effect. Settings and Design: Both extracts will be tested on isolated thoracic aorta rings of WKY and SHR. The involvement of autonomic receptors and nitric oxide will be elucidated using respective blockers. Materials and Methods: Isolated thoracic aorta rings from WKY and SHR were mounted onto myograph chambers to measure changes in the aorta tension. Increasing concentrations of AESP and MESP, from 1 µg/ml to 10 mg/ml were added onto the myograph chambers. Blockers such as atropine (1 µM), phentolamine (1 µM), propranolol (1 µM), and Nω‑nitro‑l‑arginine methyl ester (100 µM) were preincubated before addition of extracts to check for involvement of muscarinic, α‑ and β‑adrenergic receptors (AR) as well as nitric oxide, respectively. Statistical Analysis Used: Two‑way ANOVA, followed by post hoc Bonferroni test was used, where P < 0.05 (two‑tailed) was considered statistically significant. Results: AESP and MESP caused significant vasorelaxations through nitric oxide pathway. The former was mediated through α‑AR while the latter was mediated by β‑adrenergic and muscarinic receptors. Conclusion: Vasorelaxation effect by AESP and MESP involved nitric oxide pathway which is possibly mediated by the autonomic receptors.